Genotoxicity test of propolis extract, mineral trioksida aggregat, and calcium hydroxide on fibroblast BHK-21 cell cultures - Ceples Dian Kartika W.P; Sri Kunarti; Ari Subiyanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Health industry has always used natural products as an alternative. Propolis, a natural antibiotic, is a resinous yellow brown or dark brown substance derived from honey bees (Apis mellifera). The main chemical compounds contained in propolis are flavonoids, phenolics and other various aromatic compounds. Flavonoids are well known plant compounds that have antibacterial, antifungal, antiviral, antioxidant and anti-inflammatory proprieties. Propolis is expected to be an alternative used for root canal treatment with lower toxicity compared to calcium hydroxide (Ca(OH)2 . Over the last decade, a new material, mineral trioxide aggregate (MTA) was developed, and has been used as the gold standard. All materials used in mouth should be biocompatible. The initial level of material biocompatibility evaluation involves toxicity and genotoxicity tests. Purpose: This research is aimed to conduct comparison test of genotoxicity effect of propolis extract, MTA and Ca(OH)2 on fibroblast BHK-21 cell culture. Methods: This research was conducted with single-cell gel electrophoresis method. Results: The results indicate that propolis extract cannot cause DNA damage, while MTA can cause apoptosis and Ca(OH)2 can cause neucrosis. Conclusion: It can be concluded that propolis extract has genotoxicity effect lower than MTA and Ca(OH)2 , but MTA has lower effect on fibroblast BHK-21 cell culture.